Nepotisme Perspektif Al-Qur’an dalam QS. al-Nisā’ [4]: 58 Analisis terhadap Hermeneutika Double Movement Fazlur Rahman - Khairul Fahmi Rizki, Muhammad; Nurusshobah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The adagium ṣāliḥ li kulli zamān wa makān attributed to the Qur’an affirms its inevitable relevance in responding to the ever-evolving dynamics of life, including the issue of nepotism. Nepotism is a form of distortion of social justice that undermines social, political, and economic systems in many countries, including Indonesia. Therefore, a contemporary approach is needed to understand the messages of the Qur’an so that its universal values can be applied contextually. This study employs a library research method with the hermeneutical approach of Fazlur Rahman’s double movement. This approach involves two main movements: first, exploring the meaning of Qur’anic texts within their socio-historical context; and second, applying their universal moral values to the present context. The findings show that QS. al-Nisā’ [4]: 58, through the first movement, generates two moral ideas: justice (al-‘adālah) and trustworthiness (al-amānah). The second movement emphasizes the importance of implementing these values in social, political, and governmental life. Thus, the teachings of the Qur’an can be actualized contextually as an ethical foundation for preventing and addressing nepotism in a sustainable manner across various aspects of life